2013
DOI: 10.1186/1471-2253-13-13
|View full text |Cite
|
Sign up to set email alerts
|

KPC - 3 Klebsiella pneumoniaeST258 clone infection in postoperative abdominal surgery patients in an intensive care setting: analysis of a case series of 30 patients

Abstract: BackgroundAbdominal surgery carries significant morbidity and mortality, which is in turn associated with an enormous use of healthcare resources. We describe the clinical course of 30 Intensive Care Unit (ICU) patients who underwent abdominal surgery and showed severe infections caused by Klebsiella pneumoniae sequence type (ST) 258 producing K. pneumoniae carbapenemase (KPC-Kp). The aim was to evaluate risk factors for mortality and the impact of a combination therapy of colistin plus recommended regimen or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 24 publications
3
54
0
1
Order By: Relevance
“…(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). The pitfalls of this disease are the doubtful diagnosis in its early stage in which it can be mimicking different digestive diseases, even functional, (23)(24)(25)(26)(27) and, subsequently, a possible evolution in severe peritonitis and sepsis (28)(29)(30)(31). As a consequence, although the appendectomy is considered a simple and safe procedure, a reliable diagnosis and a safe and correct surgical procedure are needed (32).…”
Section: Discussionmentioning
confidence: 99%
“…(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). The pitfalls of this disease are the doubtful diagnosis in its early stage in which it can be mimicking different digestive diseases, even functional, (23)(24)(25)(26)(27) and, subsequently, a possible evolution in severe peritonitis and sepsis (28)(29)(30)(31). As a consequence, although the appendectomy is considered a simple and safe procedure, a reliable diagnosis and a safe and correct surgical procedure are needed (32).…”
Section: Discussionmentioning
confidence: 99%
“…88 The greatest increased risk was in patients with ventilatorassociated pneumonia (VAP), a non-FDA approved indication but a common type of CRE infection. PK-PD analysis from a hospital-acquired pneumonia study showed the mean AUC observed in patients with VAP was 15% lower and the MIC 50 and MIC 90 were higher compared to patients without VAP and therefore the median fAUC/MIC ratios were only 1.73 and 4.39 for patients with VAP and HAP, respectively. 87 A subsequent phase 2 study in patients with HAP evaluating 2 higher dose regimens of tigecycline suggested better PK-PD target attainment and clinical efficacy compared to standard doses although the small number of patients enrolled limits the interpretation of the results.…”
Section: Tigecyclinementioning
confidence: 99%
“…100 Achievement of this PK-PD target can be challenging in treating infections due to CRE due to the elevated MICs. For example, the CLSI breakpoint for amikacin is 16 mg/ml and the MIC 90 for CRE isolates is often at the breakpoint or above. 93 Therefore to achieve the PK-PD target of a peak concentration 8-10 times the MIC, the goal peak concentration would be 128-160 mg/ml.…”
Section: Aminoglycosidesmentioning
confidence: 99%
See 2 more Smart Citations